Characteristics associated with the risk of psychosis among immigrants and their descendants in France. Issue 5 (9th April 2021) - Tortelli, Andrea; Simon, Patrick; Lehouelleur, Sophie; Skurnik, Norbert; Richard, Jean Romain; Baudin, Grégoire; Ferchiou, Aziz; Leboyer, Marion; Schürhoff, Franck; Szöke, Andrei
Abstract: Objective: To explore the sociodemographic characteristics that might explain the increased incidence of psychosis among immigrants and their descendants in France. Methods: Data were collected for all subjects with first contact for psychosis aged between 18 and 64 years, in two catchment areas in the Paris region. Incidence rates (IR) and incidence rate ratios (IRR) were adjusted for gender and age. Results: During 805, 396 persons‐year at risk, we identified 321 cases of first‐episode psychosis, of which 129 were immigrants and 78 descendants of immigrants. We found that the geographic origin was associated with the risk of psychosis although generation has little impact. Sub‐Saharan African immigrants and their descendants showed the highest risk (IRR = 3.1 and IRR = 2.9, respectively). We observed that living in deprived areas increased the incidence of psychosis (IRR = 1.3, 95CI%: 1.0–1.6), particularly among immigrants (IRR = 1.6; 95% CI: 1.1–2.5). Finally, our study showed that subjects having unstable housing (a proxy for "hard to count population") could inflate the incidence rates among immigrants. Conclusion: The current study shows that the increased risk of psychosis in groups with an immigration background in France is associated with their origin and highlights the importance of socioeconomic factors in modulating this risk. Abstract : The aim of the present study is to explore the characteristics that might explain this increase: geographic origin, generation (immigrants or their descendants), social environment, and living conditions. We observed that living in deprived areas increased the incidence of psychosis, particularly among immigrants. Geographic origin was associated with the risk of psychosis although generation has little impact and Sub‐Saharan African immigrants and their descendants showed the highest risk.